2018
DOI: 10.1182/blood-2017-10-810622
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of NFE2 overexpression in myeloproliferative neoplasms

Abstract: The transcription factor "nuclear factor erythroid 2" (NFE2) is overexpressed in the majority of patients with myeloproliferative neoplasms (MPNs). In murine models, elevated NFE2 levels cause an MPN phenotype with spontaneous leukemic transformation. However, both the molecular mechanisms leading to NFE2 overexpression and its downstream targets remain incompletely understood. Here, we show that the histone demethylase constitutes a novel NFE2 target gene. JMJD1C levels are significantly elevated in polycythe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 27 publications
0
41
1
Order By: Relevance
“…It has never been reported in association with AML(The Cancer Genome Atlas Research Network 2013) until recently, when Lazarevic et al (2018) described variants in NFE2 in 4/6 patients with isolated myeloid sarcoma. Most of these variants (including those reported here) lead to a truncated protein, contrasting with the observation that NFE2 overexpression is associated with both a myeloproliferative phenotype in animal models (Kaufmann et al, 2012) and the development of myeloid neoplasms in humans (Goerttler et al, 2005;Peeken et al, 2018). The findings by Jutzi et al (2013), however, support the role of the truncated NFE2 protein in enhancing the wild-type protein function, which could explain the potential role of the NFE2 variant in AML pathogenesis in our patient.…”
Section: Discussioncontrasting
confidence: 95%
“…It has never been reported in association with AML(The Cancer Genome Atlas Research Network 2013) until recently, when Lazarevic et al (2018) described variants in NFE2 in 4/6 patients with isolated myeloid sarcoma. Most of these variants (including those reported here) lead to a truncated protein, contrasting with the observation that NFE2 overexpression is associated with both a myeloproliferative phenotype in animal models (Kaufmann et al, 2012) and the development of myeloid neoplasms in humans (Goerttler et al, 2005;Peeken et al, 2018). The findings by Jutzi et al (2013), however, support the role of the truncated NFE2 protein in enhancing the wild-type protein function, which could explain the potential role of the NFE2 variant in AML pathogenesis in our patient.…”
Section: Discussioncontrasting
confidence: 95%
“…Although JMJD1C belongs to KDM3 family that in general catalyzes H3K9 demethylation, multiple independent studies published contradicting results that either succeeded 7,14,15,[22][23][24][25][26] or failed 5,6,[27][28][29] to detect the demethylating activities of JMJD1C at H3K9. Most if not all studies with negative results failed to detect H3K9 demethylating activities of JMJD1C in vitro, whereas studies with positive results detected H3K9 demethylating activities of JMJD1C in vivo using either western blot or chromatin immunoprecipitation assays.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of histone demethylases as novel targets in the treatment of myeloid malignancies is highlighted by the fact that several LSD1 inhibitors are already under clinical investigation [9] and JMJC domain-containing demethylase inhibiting substances are in development. While our previous results indicate a possible role for JMJD1C in the pathophysiology of MPN (1), its function in these disorders has not been investigated. Moreover, its role in healthy hematopoiesis remains incompletely understood and developmental expression of JMJD1C has not been examined.…”
Section: Resultsmentioning
confidence: 76%
“…We have previously shown that the histone 3 mono and dimethyl-specific demethylase JMJD1C is overexpressed in MPN patients [1]. JMJD1C participates in an auto-regulatory loop, as it is both a target of the transcription factor NFE2, overexpressed in the large majority of MPN patients, and also binds the NFE2 promoter, thereby enhancing NFE2 expression.…”
Section: Introductionmentioning
confidence: 99%